Reclaiming Indigenous Economic Development Through Participatory Action Research. Issue 1 (2nd January 2022) - Pérez Piñán, Astrid V.; Friedland, Hadley; Sayers, Judith; Murphy, Matt
ABSTRACT: Participatory, gender-sensitive processes are hailed as valuable in ensuring community perspectives shape economic development planning: to assess community needs, aspirations and to identify indicators of development based on local perspectives. In Indigenous communities, such processes may not always be taken up due to research and consultation fatigue or plain scepticism. Women are often silent or less outspoken in public settings, and dominant perspectives tend to occupy most of the space and time allocated to participatory processes. This can lead to distorted understandings of community voices and inadvertently preserve the gendered status quo. A case study based on the community engagement approach taken in partnership with the government of the Toquaht Nation, on Vancouver Island endeavoured in a gender-sensitive consultation process to develop a value-based decision support system for economic development activities. The article details the use of the "Making Connections" method to facilitate discussions about economic development through Toquaht women's circles. "Making Connections" is a tool to identify and build place-based, people-centred visions and indicators of economic development for community well-being. Based on James Tully's work on actions for and of freedom, the article introduces this new method as a framework for cooperative community discussions in ways that allow for naming past and current histories of discrimination and disconnection, while honouring people's strengths, resistance and resilience. The themes and concerns emerging from the women's circles speak of a richer and more expansive notion of economic development that puts comprehensive well-being at the heart of economic development.